2019
DOI: 10.1177/1074295619835207
|View full text |Cite
|
Sign up to set email alerts
|

Using Technology to Increase Opportunities to Respond

Abstract: Delivering high rates of opportunities to respond (OTR) has been shown to improve student outcomes for students with challenging behavior. High rates of OTR can maximize student engagement while providing ways for teachers to quickly assess student content mastery. Given the increasing trend of technology use in schools, teachers can leverage technology for delivering OTR. We discuss three technology-based tools teachers can use to enhance OTR delivery with examples of how to incorporate these tools into class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…For decades, research has consistently shown that ASR promotes learning (e.g., Malanga and Sweeney 2008;Pratton and Hales 1986;Zayac et al 2016). In traditional classrooms there are a multitude of ways to provide students with opportunities to respond (OTR) (Menzies et al 2017;Rila et al 2019; for review, see Common et al 2020;Van Camp et al 2020) including hand raising (e.g., Landrum 2015), response cards (e.g., Gardner et al 1994;Marmolejo et al 2004;Randoph 2007), choral responding (Haydon and Hunter 2011;Haydon et al 2010) and using "clickers" to answer questions (e.g., Dallaire 2011;Kay and LeSage 2009). Interestingly, although the particular modality of ASR does not appear to influence student learning (Zayac et al 2016), the type of technology used can have an effect on participation rates.…”
Section: Active Student Respondingmentioning
confidence: 99%
“…For decades, research has consistently shown that ASR promotes learning (e.g., Malanga and Sweeney 2008;Pratton and Hales 1986;Zayac et al 2016). In traditional classrooms there are a multitude of ways to provide students with opportunities to respond (OTR) (Menzies et al 2017;Rila et al 2019; for review, see Common et al 2020;Van Camp et al 2020) including hand raising (e.g., Landrum 2015), response cards (e.g., Gardner et al 1994;Marmolejo et al 2004;Randoph 2007), choral responding (Haydon and Hunter 2011;Haydon et al 2010) and using "clickers" to answer questions (e.g., Dallaire 2011;Kay and LeSage 2009). Interestingly, although the particular modality of ASR does not appear to influence student learning (Zayac et al 2016), the type of technology used can have an effect on participation rates.…”
Section: Active Student Respondingmentioning
confidence: 99%
“…Recently, Rila and colleagues (2019) discussed how delivering high rates of OTR is shown to improve student outcomes for students with challenging behaviors and how those high rates of OTR can maximize student engagement while allowing students to work toward mastering instructional content. Rila et al (2019) stated that if students are off task, inattentive, or disruptive during instruction, they are more likely to be excluded from classroom activities and fall behind academically.…”
Section: Active Student Respondingmentioning
confidence: 99%
“…In the following sections we describe three technologies that can be used to increase student responding. In addition, we provide steps and description of each technology following a task analysis model suggested by Rila and colleagues (2019).…”
Section: Using Electronic Asr Toolsmentioning
confidence: 99%
“…There are a variety of technology-based tools designed for use in the classroom to deliver OTRs and increase student responses (Ault & Horn, 2018; Rila, Estrapala, & Bruhn, 2019). Rila et al (2019) provided a step-by-step guide for using three different programs (i.e., Plickers, Kahoot, Socrative). The following section highlights the use of a fourth program, Poll Everywhere.…”
Section: Teacher-directed Opportunities To Respondmentioning
confidence: 99%